Kerjasama Guru PAI dan Orang Tua Dalam Membina Karakter Religius Peserta Didik Di SD 05 Padang Tarok Kecamatan Baso Kabupaten Agam - Annisa Sri Lestari; Charles; Wedra Aprison; Salmi Wati (KOLONI, 2022)
The background of this research is that there has not been a good collaboration between parents and teachers in fostering the religious character of students. Where there are still many students who do not pray and behave inappropriately, in fostering the morals of students, cooperation between parents and teachers is needed. The type of research carried out is field research (Field Research) with a qualitative descriptive approach. This qualitative descriptive method is a research conducted to describe and analyze phenomena that occur in the field. The key informants in this study were Islamic Religious Education Teachers and the supporting informants were the parents of students at SD 05 Pdang Tarok. To collect data, the authors conducted interviews and documentation, and to measure the validity of the data triangulated the data by checking the validity of the data using something else in comparing the results of interviews with the object of research. From the research that the author has done, it can be concluded that in the implementation of cooperation between PAI teachers and parents, they have carried out various ways: 1) communication between teachers and parents, 2) correspondence, 3) communication by telephone, 4) involving parents with school affairs. In doing cooperation between teachers and parents, they have tried to do as much as possible, but there are still factors that hinder the course of the cooperation. Where the factors that inhibit the cooperation of teachers and parents are 1) lack of attention from parents, 2) the ability of teachers, 3) the community environment is not good.  Keywords: Cooperation between PAI Teachers and Parents, Religious Character